2019
DOI: 10.3233/jad-190331
|View full text |Cite
|
Sign up to set email alerts
|

Air Pollution, Combustion and Friction Derived Nanoparticles, and Alzheimer’s Disease in Urban Children and Young Adults

Abstract: Exposures to fine particulate matter (PM 2.5 ) and ozone (O 3 ) ≥US EPA standards are associated with Alzheimer's disease (AD) risk. The projection of 13.8 million AD cases in the US by the year 2050 obligate us to explore early environmental exposures as contributors to AD risk and pathogenesis. Metropolitan Mexico City children and young adults have lifetime exposures to PM 2.5 and O 3 , and AD starting in the brainstem and olfactory bulb is relentlessly progressing in the first two decades of life. Magneti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 120 publications
0
21
0
Order By: Relevance
“… 69 We have described the presence of magnetite nanoparticles (NPs) in frontal cortex and hearts of MMC subjects often associated with other non-endogenous metals (including platinum, cadmium, cerium). 70 , 71 Indeed, NPs 72 are abundant in MMC air and contain metals, including Fe, Pb or Zn. 73 Villahermosa residents exposed mainly to -PM 2.5 rich in PAHs emitted from the flaring of source gas and incineration of oil condensates from gas- and oil extraction activities and from uncontrolled biomass burning, are having the lowest Tinetti gait scores, while MMC residents, are worse in balance and are being exposed to primary and secondary PM 2.5 associated with heavy duty diesel vehicles and the photochemical activity of the region.…”
Section: Discussionmentioning
confidence: 99%
“… 69 We have described the presence of magnetite nanoparticles (NPs) in frontal cortex and hearts of MMC subjects often associated with other non-endogenous metals (including platinum, cadmium, cerium). 70 , 71 Indeed, NPs 72 are abundant in MMC air and contain metals, including Fe, Pb or Zn. 73 Villahermosa residents exposed mainly to -PM 2.5 rich in PAHs emitted from the flaring of source gas and incineration of oil condensates from gas- and oil extraction activities and from uncontrolled biomass burning, are having the lowest Tinetti gait scores, while MMC residents, are worse in balance and are being exposed to primary and secondary PM 2.5 associated with heavy duty diesel vehicles and the photochemical activity of the region.…”
Section: Discussionmentioning
confidence: 99%
“…In healthy individuals, protein misfolding may occur early in life, and chronic exposure to air pollutants might accelerate the protein aggregation. It has been also suggested that AD and PD pathology may occur in the olfactory bulbs as a result of inhalation of air pollutants (Calderón-Garcidueñas et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Excessive axonal Ca 2+ influx induces Wallerian axonal degeneration, and excessive cytoplasmic Ca 2+ influx induces excitotoxicity [346][347][348][349]. Olfactory sensory neurons are exposed to multiple sporadic AD risk factors, including combustion-derived carbon nanoparticles and microbial toxins [350][351][352][353]. AD pathogenic factors spread between neurons trans-synaptically in extracellular vesicles, such as exosomes [354][355][356][357][358], and tau pathology spreads through the brain in AD in a stereotypical fashion [2].…”
Section: Pf-04447943 and Bi 409306mentioning
confidence: 99%
“…AD pathogenic factors spread between neurons trans-synaptically in extracellular vesicles, such as exosomes [354][355][356][357][358], and tau pathology spreads through the brain in AD in a stereotypical fashion [2]. Olfactory sensory neurons' axons project into the olfactory bulb [359], a brain region that is critically affected starting from the preclinical stages of AD [350,351]. Thus, PDE9A inhibition might promote pGC/cGMP-activated CNG-mediated Ca 2+ influx into olfactory sensory neurons, axon degeneration, excitotoxicity, and possibly propagation of AD pathologies to the olfactory bulb, possibly counterbalancing its positive effects and providing no net change in AD patients taking PDE9 inhibitors.…”
Section: Pf-04447943 and Bi 409306mentioning
confidence: 99%